The Birds of Pakistan : Passeriformes: Pittas to Buntings (vol. 2) - Roberts T. J. (Karachi Oxford University Press, 1992)
This work concludes noted ornithologist Tom Roberts' magnificent survey of the birds of Pakistan. Together with Volume 1, the work covers 660 species, offering detailed descriptions of each, supported by 47 full-page plates and over 100 black and white illustrations drawn by the author. Distribution maps of over 570 species detail wintering or breeding status, and voice descriptions are drawn from the author's own extensive collection of bird recordings made in Pakistan during his 34 years of residence in that country. Each volume contains a bibliography and index. Amateur and professional ornithologists alike will appreciate this unique work of art and scholarship.
Include Maps, Illustrations, Bibliography and Index.
Keywords: Pakistan -- Birds -- Birds--Geographical distribution